School-Based Support for Monitoring the Nutritional Status of Primary School: Initial Reflections on the Implementation of the Free Nutritious Meals Programme as a Tool for Human Resource Development - Nayla Desviona; Lizabeth Sari Dewi; Asramid Yasin; Mario Zulhadi Amrullah; Viola Novaryca; Ika Dwimaya Roza; Deby Aisyah Rj Nur; Wella Sandria (Fakultas Teknik Universitas Cenderawasih, 2026)
Nutritional problems among school-age children remain an important challenge in human resource development in Indonesia. Adequate nutritional status is essential for supporting physical growth, cognitive development, learning achievement, and future productivity. Schools play a strategic role in promoting children's health through nutritional monitoring and educational interventions, particularly during the implementation of the Free Nutritious Meal Program (MBG). This community service activity aimed to monitor students’ nutritional status and strengthen awareness of the importance of nutrition as a foundation for human resource development. The activity was conducted on April 5–6, 2026, at SD Negeri 09 Jambi City and involved 261 students from grades I to III. A school-based assistance approach was implemented through anthropometric measurements, including body weight and height assessments, followed by balanced nutrition education. The findings revealed that 77.0% of students had normal nutritional status, while 8.8% were undernourished, 9.6% were overweight, and 4.6% were classified as obese. The activity also increased school awareness regarding the importance of continuous nutritional monitoring and evidence-based health management. These findings suggest that school-based nutritional monitoring can support the implementation of the Free Nutritious Meal Program and serve as an initial effort to strengthen human resource development by fostering healthier, more productive, and higher-quality future generations.